1995
DOI: 10.1164/ajrccm.151.4.7697276
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral application of a Pseudomonas aeruginosa flagella vaccine elicits specific anti-flagella antibodies in the airways of healthy individuals.

Abstract: To test the hypothesis that a Pseudomonas aeruginosa flagella (FLA) vaccine, intramuscularly administered, elicits specific antibodies in the respiratory tract, antibody titers against FLA were determined in sera and bronchoalveolar lavage (BAL) fluids of 10 healthy human adults before and after immunization. Immunization produced significantly increased anti-FLA antibody titers in all sera (mean reciprocal titers: IgG: 26,711; IgA: 2,767; IgM: 421) and on respiratory epithelial lining fluids (mean reciprocal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Our previous studies of this acute pneumonia model indicated that death from pneumonia was highly correlated with systemic spread of bacteria (1). It therefore follows that survival of the PAO1⌬aroA-immunized mice is due to prevention of the dis- (8,23,31), on outer membrane proteins (27,32,40) and, more recently, on the PcrV antigen component of the type III secretion system (15,24,55,57). We note that, in these later studies, protection against lethal pneumonia has only been demonstrated with P. aeruginosa strain PA103, a highly virulent, ExoU ϩ strain that can be given to mice at a relatively low inoculum to generate lethality.…”
Section: Discussionmentioning
confidence: 84%
“…Our previous studies of this acute pneumonia model indicated that death from pneumonia was highly correlated with systemic spread of bacteria (1). It therefore follows that survival of the PAO1⌬aroA-immunized mice is due to prevention of the dis- (8,23,31), on outer membrane proteins (27,32,40) and, more recently, on the PcrV antigen component of the type III secretion system (15,24,55,57). We note that, in these later studies, protection against lethal pneumonia has only been demonstrated with P. aeruginosa strain PA103, a highly virulent, ExoU ϩ strain that can be given to mice at a relatively low inoculum to generate lethality.…”
Section: Discussionmentioning
confidence: 84%
“…A monovalent P. aeruginosa lagella vaccine was safe and immunogenic in healthy human adults by intramuscular immunization and showed high and long-lasting serum antibody (IgG and IgA) titers against lagella positive P. aeruginosa [130].…”
Section: Antibody and Vaccine Development Against Lagellins And Pilinsmentioning
confidence: 99%
“…78,79 Intramuscular administration of a monovalent P. aeruginosa flagella vaccine was well tolerated in healthy volunteers and elicited high and long-lasting systemic and lung antibody titers. 80 In a double-blind, placebocontrolled, randomized, multicenter phase III trial on 483 CF patients without P. aeruginosa colonization 4 intramuscular injections of a bivalent P. aeruginosa flagella vaccine were given Elastase and alkaline proteases interfere with the host immune system by cleaving immunoglobulins, 112,113 inhibiting cytokines, 114,115 and interfering with the immune cell functions. [116][117][118] Immunization with elastase and alkaline protease toxoids were effective in P. aeruginosa infection models of hemorrhagic pneumonia in minks, 119 corneal ulcers 120 and burns in mice.…”
Section: Flagellamentioning
confidence: 99%